Clinical Analysis of Congenital Deficient Tracheal Cartilage Rings: Six Case Reports and a Literature Review - Ma, Jing; Meng, Chen; Feng, Zhiyu; Han, Xiaorong; Liu, Shuaishuai; Liu, Na; Zhu, Weiwei (Frontiers in Pediatrics, 2020)
Congenital deficiency of tracheal rings is a rare tracheal malformation that can cause central airway obstruction. Herein, we reported the clinical data of six patients with symptomatic congenital deficient tracheal rings. There were five cases with isolated short-segment absent cartilage ring located on the distal trachea (three cases), cervical trachea (one case), and distal trachea combined with bilateral bronchi (one case). Among them, four (4/5) received surgical tracheal resection; three fully recovered, and one died of severe infection. Besides, one patient, who could not be weaned off the ventilation, died after rejecting surgery. One case had episodes of recurrent dyspnea and extubation failure due to long-segment tracheomalacia after repair of esophageal atresia (EA) and tracheoesophageal fistula (TEF). For this patient, deficient cartilage rings were suspected and confirmed at the age of 26 months. Moreover, the clinical characteristics of twelve cases with congenital deficient tracheal cartilage rings reported in the previous literature were reviewed. The different characteristics between short and long segment deficient cartilage rings were discussed.